2011
DOI: 10.1287/mnsc.1100.1307
|View full text |Cite
|
Sign up to set email alerts
|

Generating Ambiguity in the Laboratory

Abstract: This article develops a method for drawing samples from a distribution with no finite quantiles or moments. The method provides researchers with a way to give subjects the experience of ambiguity. In any experiment, learning the distribution from experience is impossible for the subjects, essentially because it is impossible for the experimenter. We characterize our method, illustrate it in simulations, and then test it in a laboratory experiment. Our method does not withhold sampling information, does not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This is consistent with the assumption that, similar to WTP, the WTA of the risky prospect is easier to determine and therefore more likely to serve as a reference point in the WTA task. Stecher et al (2011) similarly found no systematic preference reversals beyond noise for WTA under ambiguity.…”
Section: Discussionmentioning
confidence: 87%
“…This is consistent with the assumption that, similar to WTP, the WTA of the risky prospect is easier to determine and therefore more likely to serve as a reference point in the WTA task. Stecher et al (2011) similarly found no systematic preference reversals beyond noise for WTA under ambiguity.…”
Section: Discussionmentioning
confidence: 87%
“…It is more interesting to study natural sources of uncertainty. For an emotion-neutral source of ambiguity, the ambiguity-generator of Stecher, Shields, & Dickhaut (2011) may serve better than Ellsberg urns or probability intervals where information is concealed for subjects, but we here focus on traditional stimuli. Baillon et al (2016) introduce new indexes of ambiguity attitudes for natural events without symmetries.…”
Section: Discussion Of Experimental Detailsmentioning
confidence: 99%
“…The number of payoffs (N ) was fixed at 5, though subjects were not given this information. 5 We used the procedure in Stecher et al (2011) to generate the ambiguous distributed payoffs. This procedure creates complete ambiguity for subjects as they have no way to put any probabilities on the payoffs.…”
Section: Experimental Designmentioning
confidence: 99%